TRAIL inhibits platelet-induced colorectal cancer cell invasion. Issue 2 (February 2019) - Wu, Li-Sha; Wang, Xiao-Wei; He, Wen; Ma, Xiao-Ting; Wang, Hai-Yue; Han, Mei; Li, Bing-Hui
Objective: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a pro-apoptotic ligand that activates the extrinsic apoptosis pathway of cell death receptors. This study aimed to evaluate the relationship between TRAIL and platelet-induced tumor metastasis in colorectal cancer. Methods: Platelet P-selectin (CD62P) was measured by immunohistochemistry in tumor and adjacent normal tissues from 90 patients with colorectal cancer undergoing resection. Tumor cell invasion was assessed by transwell assay in the presence of platelets with or without TRAIL. The expression of TRAIL receptors DR4 and DR5 on platelets was assessed by flow cytometry, real-time polymerase chain reaction, and western blotting. Results: P-selectin (CD62P) expression was significantly increased in tumor tissues compared with adjacent normal tissues. High CD62P expression was significantly correlated with tumor stage and vascular invasion. Tumor cell migration was increased by coculture with platelets, but this effect was inhibited by TRAIL. Transforming growth factor (TGF)-β1 secretion was significantly reduced in TRAIL-treated platelets. The TRAIL receptor DR5 but not DR4 was expressed in platelets according to flow cytometry. Conclusions: TRAIL could inhibit metastasis and colon cancer cell invasion by promoting platelet apoptosis and reducing the release of TGF-β1.